Traumatic pediatric atlantoaxial rotatory dislocation successfully reduced with 1 month total of halter traction: a case report - Ab. Wahid, Hazwan; Kow, Ren Yi; Mor Japar Khan, Ed Simor Khan; Komahen, Colin (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
The occurrence of atlantoaxial rotatory subluxation is fairly uncommon; however, it is more common to be encountered in the paediatric population, typically seen after a retropharyngeal inflammation or after a minor trauma. Ligamentous laxity, shallower and more horizontally oriented facet joints especially at the C1-2 joint making them prone to have atlantoaxial subluxation or dislocation. If recognized early it can be successfully managed non-surgically before chronic inflammatory changes affect the ligaments and joint structure of the C1-2 complex. However, there is no standard treatment protocol as some authors like Nael et al and Haliasos and Norris recommended more invasive Halo skull traction. Thus, we report this case managed with less invasive Halter traction with no risk of pin site infections. We present the case of a 12-year-old Malay boy with traumatic atlantoaxial dislocation who came to us after he slipped and fell, presented with neck pain and torticollis to the left side but without other neurological deficits. A computed-tomography (CT) scan revealed an atlantoaxial rotation of 47 to the left without any signs of osseous lesions. MRI was also done and all ligaments were intact. The neck was then reduced by cautious rotation with Halter traction with the cervical spine in the neutral position with slight flexion thus avoiding harm by potential posttraumatic disc lesions. The patient was put on Halter traction for a total of one month. Post-traction revealed full range of motion of the neck without any tenderness, head and neck alignment restored to neutral position. In the children population, atlantoaxial subluxation is a rare condition but is severe if left untreated. Early treatment implies a non-surgical approach and a good outcome is observed in our case as well as reported by other authors.